Diagnostic Accuracy of Serum Carbohydrate Antigen 19-9 in Determining Etiology of Obstructive Jaundice (BIRDEM Medical Journal, 2017)
Background: Serum carbohydrate antigen 19-9 (CA 19-9), a tumour marker for malignancies of the hepatobiliary tract and pancreas, frequently elevated in a number of non-malignant conditions that are associated with jaundice. The CA 19-9 tends to normalize following the restoration of biliary drainage. This study was designed to assess the clinical application of CA19-9 in diagnosing pancreatobiliary malignancies in patients with obstructive jaundice and in discriminating between benign and malignant causes.Methods: Sixty three patients presented with obstructive jaundice on the basis of clinical, biochemical and imaging methods with elevated CA 19-9 were included in this study. Serum CA 19-9 levels were measured on admission and two weeks following endoscopic biliary drainage performed through an ERCP procedure at the department of Gastrointestinal, hepatobiliary and pancreatic disorders (GHPD) of BIRDEM general hospital. Malignant and benign cases were differentiated by ultrasonogram, CT scan, MRCP and morphological findings during ERCP procedure. Diagnostic accuracy of CA19-9 in the detection of malignancy was estimated by the receiver operating characteristic (ROC) curve.Results: Age was 53.76±14.48 years (mean±SD) and sex was 32:31 (M:F). Median value of CA 19-9 in malignant cases was higher (1000 U/ml) than benign cases (93 U/ml) (p=0.001). After biliary drainage serum CA19-9 levels normalized in 15(50%) benign and 1(3%) malignant cases (p=0.001). The AUC of CA 19-9 was 0.825. Sensitivity, specificity, PPV and NPV at cut off value 90 U/ml were 100, 50, 68.8 and 100; at 100 U/ml were 100, 53.3, 70.2 and 100; at 200 U/ml were 90.9, 66.7, 75 and 87, at 500 U/ml were 63.6, 76.7,75 and 65.7 respectively. Diagnostic accuracy of CA 19-9 was observed more at cut off value 200 U/ml.Conclusions: Deranged CA19-9 is frequently observed in benign conditions with jaundice and shown to normalize following improvement of biliary drainage. Caution is necessary in the interpretation of an elevated serum CA 19-9 value as a marker for malignancy, especially in patients with benign cholestasis.Birdem Med J 2017; 7(2): 95-100